THE PROCESSES OF “CREATIVE DESTRUCTION” AND DEVELOPMENT OF ECONOMY IN THE INDEPENDENT UKRAINE - I. Egorov; N. Lynchevs’ka (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper deals with the issue of transformation processes in the Ukrainian economy in the years of independence in the context Schumpeterian concept of transformation. It is shown that initial parameters of these processes have been assessed incorrectly; practical managerial, aimed at implementation of changes, were incomplete and poorly organized. This, in turn, has led to substantial negative consequences for the national economy.